Environmental health experiences in prolonged displacement: A systematic scoping review of challenges and interventions in low- and middle-income countries (LMICs) - Iqbal, Kashif; Liang, Hu; Alam, Sunana; Asif, Muhammad (Dynamics of Rural Society Journal, 2026)
Providing adequate environmental health services is crucial in contexts of forced displacement, where over 70 million people—mostly in urban or informal settlements—often face prolonged displacement with limited access to water, sanitation, and hygiene (WaSH). The presence of these unmet needs of environmental health leads to a greater likelihood of falling sick, social unrest, and long-term inequality. Although the magnitude of the crisis is tremendous, there is a lack of in-depth understanding of the environmental health situation and responses in the context of long-term displacement. The proposed article will thus synthesize the currently available knowledge base on environmental health in prolonged displacement contexts, identify key conditions and issues, and provide suggestions for future action. This study employed a systematic scoping review methodology that adhered to the PRISMA guidelines. A search was conducted of 212 peer-reviewed studies, institutional reports (also known as gray literature, which refers to materials published outside of academic journals, such as NGO reports and working papers). The findings indicate that research on water, sanitation, and overcrowding has found substantial evidence, whereas other environmental health domains, including waste disposal, feminine hygiene, and air quality, have extremely low representation. Issues that have been faced are institutional fragmentation, lack of funds, and political constraints, which impede the sustainable provision of services. Excessive exposure to waterborne and respiratory diseases, as well as poor environmental conditions and failure to adhere to international humanitarian standards, are also highlighted as significant issues in the review. The paper emphasizes the importance of inclusive environmental health policies, enhanced stakeholder collaboration, and ongoing planning and management. It recommends integrating displaced populations into national systems, prioritizing critical health areas, and strengthening evidence to guide policy and practice—key steps to ensuring dignity, equity, and resilience in protracted displacement.